The Identification of single nucleotide polymorphisms in GnRH-I, GnRH-II/MRPS26, GnRHR exons and their Association with egg production in Anand Synthetic White Leghorn and Anand Bantamised White Leghorn Chicken - Pal, Sourav; Patel, Ashish C.; Hinsu, Ankit T.; Panchal, Ketankumar J.; Koringa, Prakash G.; Rank, Dharamsibhai N. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The aim of study was to identify Single Nucleotide Polymorphisms (SNPs) in the exon regions of GnRH-I, GnRH-II/MRPS26 and GnRHR genes and to assess their association with egg production up to 64 weeks of age (EN64) in chicken. Blood samples were collected from 48 Anand Synthetic White Leghorn (ASWLH) and 48 Anand Bantamised White Leghorn (ABWLH) chicken. Custom panel was designed for these genes’ exon regions and amplicon sequencing was performed on Illumina Miseq platform. Total 41 SNPs (19 previously reported and 22 novel SNPs) were identified from 96 samples. Association analysis revealed that rs314996211 (p
Keywords: SNP; chicken; egg production; GnRH; amplicon sequencing; white leghorn